LITHOSTRATIGRAPHY AND GEOCHEMICAL CHARACTERIZATION OF LIMESTONE DEPOSITS AROUND KUSHIMAGA AREA IN YOBE OF NORTH-EASTERN NIGERIA (Nigerian Journal of Technology, 2018)
This study presents detailed petrographic and chemical compositional characteristic of limestone deposits for possible industrial uses and specifications. The study area falls within the Gongola basin, North-eastern Nigeria. Core limestone samples were collected from four boreholes at the depth of approximately 25 metres each in Kushimaga area around Gulani in Yobe state; north-eastern Nigeria. Lithological units were observed in the following sequence; topsoil and clay with an average thickness of 1.513m, limestone 5.553m, shale 7.853m respectively. Eleven limestone samples were selected from the boreholes for petrography and chemical analysis (Fluorescence Spectroscopy analysis). From the petrograhic studies the limestone samples are composed (visual estimate) of over 95% calcite, trace amounts of colourless already recrystallized fossil of planktonic forams and mollusc, weakly deformed greenish grains of glauconite about 0.2 to 0.3 mm in grain size, traces of opaque, isotropic, high relief iron oxide minerals with 0.03 to 0.5 mm grains sizes are present disseminated in the form of limonite. Traces of quartz and feldspar grains of silt size class were also noted in thin sections. With less than 10% grains the samples are classified as mudstone. The results of chemical analyses of limestone shows a range values of SiO2, 10.05wt% to 32.00wt% , CaO, 21.00wt% to 53.99wt%, MgO, 0.35wt% to 1.00wt%,  Al2O3, 2.15wt% to 12.69wt%, Fe2O3, 1.28wt% to 4.90wt%, Na2O, 0.002wt% to 0.18wt%, K2O, 0.9wt% to 1.96wt%, TiO2, 0.21wt% to 1.00wt%, P2O5, 0.17wt% to 0.69wt%, MnO, 0.21wt% to 0.55wt%, loss on ignition, 21.98% to 36.87%, while the result of chemical classification of the limestone show a range of Ca/Mg, 23.33% to 125.68% and Mg/Ca, 0.00% to 0.04% of the Kushimaga limestone. However, the limestone beds of the research area were compared with other standard chemical industrial specifications. The study revealed that the limestone around Kushimaga area satisfies the chemical factors for Portland cement production but falls below the standard chemical specifications for other industrial uses; glass, sugar and Paint pigments and filler productions.http://dx.doi.org/10.4314/njt.v37i4.5